Review of the influence of copper and chromium substitution on crystal structure, magnetic properties and magnetocaloric effect of GdFe2−x(Cu, Cr)x (x = 0, 0.1, 0.15 and 0.2) intermetallic compounds. (January 2022) - Saidi, M.; Bessais, L.; Jemmali, M.
Abstract: The iron-based compounds GdFe2− x (Cu, Cr) x ( x = 0, 0.1, 0.15 and 0.2) were synthesized successfully by means of arc-melting and annealing at 800 °C for one week. The structural, magnetic and magnetocaloric properties of these intermetallic compounds were investigated systematically in detail using X-ray powder diffraction (XRD) analysis, Scanning electron microscopy (SEM) equipped with Energy dispersive X-ray spectroscopy (EDS), and magnetic measurements. The Rietveld analysis of X-ray diffraction patterns proves that GdFe2− x (Cu, Cr) x ( x = 0, 0.1, 0.15 and 0.2) compounds crystallize in the cubic laves phase MgCu2 -type structure with the F d 3 ̄ m space group. Gadolinium and iron atoms statistically occupy the 8 a and 16 d sites respectively. Moreover, copper and chromium atoms substitute the iron atoms at site 8 a in the MgCu2 -type structure. The temperature dependence of magnetization studied in a broad temperature range reveals that all compounds exhibit a ferromagnetic-paramagnetic transition at Curie temperature ( T C ). We find that the substitution of iron by copper and chromium leads to a decrease in the magnetic ordering transition temperature. The Arrott plots of all our samples show the occurrence of a second-order phase transition. Besides, the performance of magnetocaloric effect (MCE) for GdFe2− x (Cu, Cr) x ( x = 0, 0.1, 0.15 and 0.2) compounds was evaluated by the magnetic entropy change (Δ S M ) and the related Relative Cooling Power (RCP). In the vicinity of T C, the Δ S M reached a maximum value of 0.79 J/kg.K, 1.2 J/kg.K, 1.4 J/kg.K and 2.5 J/kg.K, while the RCP was found to be 13.2 J/kg, 21.6 J/kg, 31.7 J/kg and 44.3 J/kg, respectively for GdFe2− x Cu x ( x = 0, 0.1, 0.15 and 0.2) compounds. Furthermore, the GdFe2− x Cr x ( x = 0.1, 0.15 and 2) compounds show Δ S M values of about 0.9 J/kg.K, 1.3 J/kg.K and 1.8 J/kg.K, and RCP values of 14.8 J/kg, 25.4 J/kg and 36.8 J/kg respectively, under a field change of 1.56 T. Through these results, the GdFe2− x (Cu, Cr) x ( x = 0, 0.1, 0.15 and 0.2) compounds can be an attractive materials for use in magnetic refrigeration and heat pumping technology above room temperature. Highlights: GdFe2 - x (Cu, Cr) x ( x = 0, 0.1, 0.15 and 0.2) samples prepared by arc melting subsequent annealing. The Rietveld analysis of XRD patterns proves that compounds crystallize in the cubic laves phase. Magnetocaloric effect at low field of GdFe2- x (Cu, Cr) x was studied for the first time. ΔS M, RCP and TEC are calculated.